2022
DOI: 10.53088/jerps.v1i3.10
|View full text |Cite
|
Sign up to set email alerts
|

Analisis pengaruh ekspor, impor, nilai tukar rupiah dan inflasi terhadap pertumbuhan ekonomi Indonesia tahun 2000- 2019

Abstract: Economic growth is a measure of progress or failure of the economy in a country, especially in Indonesia, because the level of factors of production of goods and services will affect the ongoing economic development. This study aims to determine and analyze the effect of exports, imports, the rupiah exchange rate, and inflation on economic growth in Indonesia for the 2000-2019 period. The dependent variable of this research is economic growth. In contrast, the independent variable is export, import, rupiah exc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
0
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 6 publications
1
0
0
2
Order By: Relevance
“…These results follow Research conducted by [33] which found that the variable of Export positively affected rice production in Indonesia during the period 2000-2019.…”
Section: Effect Of Exports On Rice Productionsupporting
confidence: 89%
“…These results follow Research conducted by [33] which found that the variable of Export positively affected rice production in Indonesia during the period 2000-2019.…”
Section: Effect Of Exports On Rice Productionsupporting
confidence: 89%
“…Adanya hubungan yang searah dan tidak signifikan antara inflasi dengan pertumbuhan ekonomi (Slamet & Hidayah, 2022). Hubungan yang bertolak belakang antara inflasi dan pertumbuhan ekonomi di Indonesia (Pratama & Sutrisna, 2022).…”
Section: Inflasiunclassified
“…Salah satu penelitian yang dilakukan adalah mengukur pengaruh ekspor, impor, nilai tukar rupiah, dan inflasi bagi pertumbuhan ekonomi Indonesia pada tahun 2000-2019. Penelitian tersebut menyatakan bahwa impor diperlukan karena sumber daya dalam negeri belum mampu memproduksi barang dari negara lain yang mampu memproduksi barang tersebut (Slamet & Hidayah, 2022).…”
Section: Pendahuluanunclassified